(untitled) (e-Journal of Linguistics, 2023)
The paper analyses syntax analysis in relative clause found in the novel “The Wonderful Wizard of Oz”. “The Wonderful Wizard of Oz” is a literary work of kid story by Lyman Frank Baum and the illustration was made by W.W. Denslow. Dorothy lived with her Aunt Em, Uncle Henry and her dog, Toto. Theory of relative clauses that was proposed by Quirk (1985), Sneddon (1996) and was supported by other theories. The theory used to analyze the syntax structure was the theory proposed by Brown and Miller. The method that was used to get the data was qualitative, library research. The data were taken from the novel entitled “The Wonderful Wizard of Oz”. This research study aims to: (i) analyze the syntax structure in the relative clause found in the novel entitled “The Wonderful Wizard of Oz”, (ii) analyze the types of relative clauses in the relative clauses found in the novel entitled “The Wonderful Wizard of Oz”.